Fenologia reprodutiva e distribuição espacial de Oeceoclades maculata (Lindl.) Lindl. (Orchidaceae) em Cerrado do município de Mogi Guaçu, São Paulo, Brasil - De Souza-Leal, Thiago [UNESP]; Pedroso-de-Moraes, Cristiano (My University, 2014)
Oeceoclades aculate (Lindl.) Lindl., an invasive orchid, was analyzed as to its reproductive phenology and spatial distribution, correlation between abundance of mature and immature individuals, and verifying these with microclimate patterns in the Cerrado (savanna-like vegetation) of Mogi Guaçu, São Paulo State, Brazil. For the reproductive phenology 100 plants were followed and the distribution pattern was identified by the Morisita Index (MI) and the Variance Ratio/Average ® in 20 plots of 20x10m, reduced to 10x10m afterwards. The phenology presented seasonality, with flowering from November to February, fructification from February to June, and dehiscence from June to July. Mature and immature individuals aggregated and correlated to each other, indicating dependence between the ontogenetic stages. The luminosity was the preponderant microclimatic factor in the allocation of plants. Seasonal climatic changes and intensity of anthropogenic disturbances seem to be more important for the establishment of the species than microclimate.
Reproductive phenology and spatial distribution of Oeceoclades aculate (Lindl.) Lindl. (Orchidaceae) in Cerrado of Mogi Guaçu, São Paulo, Brazil
Keywords: Alien; Orchid tropical; Savanna